Perancangan Robot Sterilisasi Barang Menggunakan Notifikasi Suara Untuk Pencegahan Penyebaran (COVID-19) - Gustomi Aldi; Khairullah Khairullah (UNIVED Press, 2022)
Corona virus infection iscalled COVID-19 (Corona Virus Disease 2019) and was first discovered in the city of Wuhan, China at the end of December 2019. This virus spreads very quickly and has spread to almost all countries, including Indonesia, in just a few months. This has made several countries implement policies to impose lockdowns in order to prevent the spread of the Corona virus. Various efforts were made to prevent the spread of the corona virus, including measuring body temperature and spraying disinfectants on humans and expedition goods. The problem that occurs is that disinfectant spraying is still done manually by officers. So it is necessary to have a disinfectant sprayer that works automatically. Disinfectant sprayer that works automatically when the infrared sensor detects items. This is also useful in preventing the spread of the corona virus. Makes it easier for officers to spray disinfectant, because it is automatic, no need to spray manually